Tempol Supplementation Restores Diaphragm Force and Metabolic Enzyme Activities in mdx Mice - David P. Burns; Izza Ali; Clement Rieux; James Healy; Greg Jasionek; Ken D. O'Halloran (MDPI AG, 2017)
Duchenne muscular dystrophy (DMD) is characterized by striated muscle weakness, cardiomyopathy, and respiratory failure. Since oxidative stress is recognized as a secondary pathology in DMD, the efficacy of antioxidant intervention, using the superoxide scavenger tempol, was examined on functional and biochemical status of dystrophin-deficient diaphragm muscle. Diaphragm muscle function was assessed, ex vivo, in adult male wild-type and dystrophin-deficient mdx mice, with and without a 14-day antioxidant intervention. The enzymatic activities of muscle citrate synthase, phosphofructokinase, and lactate dehydrogenase were assessed using spectrophotometric assays. Dystrophic diaphragm displayed mechanical dysfunction and altered biochemical status. Chronic tempol supplementation in the drinking water increased diaphragm functional capacity and citrate synthase and lactate dehydrogenase enzymatic activities, restoring all values to wild-type levels. Chronic supplementation with tempol recovers force-generating capacity and metabolic enzyme activity in mdx diaphragm. These findings may have relevance in the search for therapeutic strategies in neuromuscular disease.